LASER PHOTOCOAGULATION FOR THE TREATMENT OF OPTIC NERVE HEAD PIT–RELATED MACULOPATHY IN A PATIENT WITH BILATERAL CHORIORETINAL COLOBOMA. Issue Volume 17:Issues 2(2023) (March 2023) - Weinberger, Yehonatan; Weinberger, Dov; Priel, Ethan; Gal-Or, Orly; Ehrlich, Rita
Abstract : We report the diagnosis of a unilateral optic nerve head pit–related maculopathy, in a patient with bilateral chorioretinal coloboma, diagnosed using multimodal imaging, and treated with laser photocoagulation. Resolution of macular intraretinal and subretinal fluid and restoration of visual acuity were achieved. Abstract : Purpose: To report a case of laser photocoagulation for the treatment of a combined coloboma and optic nerve head pit–related maculopathy in a patient with bilateral chorioretinal coloboma. Methods: A case report. Results: A 15-year-old woman, presented with the visual acuity of 20/100 in her right eye for six weeks. She was diagnosed with macular detachment secondary to optic nerve head pit in her right eye and bilateral chorioretinal coloboma. Multimodal imaging, including color photography, fluorescein angiography, and spectral-domain optical coherence tomography, was used to identify and demonstrate the location of the tract of fluid from the optic nerve head pit, isolated from the coloboma. Optical coherence tomography–guided laser photocoagulation treatment at the location of the tract resulted in complete resolution of macular fluid with visual recovery to 20/25. Conclusion: Our case stresses the value of correct diagnosis directing photocoagulation treatment of combined optic nerve head pit–related maculopathy in eyes with chorioretinal coloboma using multimodal imaging.